On Polymer Expansions for Equilibrium Systems of Oscillators with Ternary Interaction - Skrypnik, W. I. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
For Gibbs lattice systems characterized by a measurable space at sites of a d-dimensional hypercubic lattice and potential energy with pair complex potential, we formulate conditions that guarantee the convergence of polymer (cluster) expansions. We establish that the Gibbs correlation functions and reduced density matrices of classical and quantum systems of linear oscillators with ternary interaction can be expressed in terms of correlation functions of these systems.